Modeling Depression in the Rat: The Development and Usefulness of a Female-centric Approach - Baker, Stephanie (Université d'Ottawa / University of Ottawa, 2011)
Women are twice as likely to suffer from depression as men, yet stress and depression research has relied primarily on the responses of males. Early life stress is hypothesized to influence the development of vulnerability to depression while adult stress exposure can act as a trigger in those predisposed. This relationship is mediated by other environmental factors. Maternal care and the social environment appear to be particularly important for mammals. The purpose of this thesis was twofold: to develop an animal model of depression for use in female rats based on the chronic mild stress (CMS) model previously validated for use in male rodents, and to apply this model in female offspring of mothers exposed to physical restraint in the second half of gestation representing an early life insult. Results indicate that a modified CMS model was able to alter hedonic and physiological responses not present in the original model. Housing condition interacted with CMS in that effects were evident only in singly housed rats. While gestational stress (GS) altered maternal weight and behavioural profiles related to offspring care and anxiety, little to no behavioural effects were noted in juvenile or adult offspring. Applying the modified CMS model to adult female offspring resulted in an anhedonic-like response that recovered rapidly prior to the third week of CMS. Weight in GS female rats was attenuated throughout life beginning post weaning. When taken together, these results demonstrate that stress-based models, previously established in males, must be altered to accommodate the hormonally intact female rat in two ways: first, to eliminate extraneous variables that may interfere with the estrous cycle and mask possible stress effects, and secondly, to consider the appropriateness of individual stressors to induce a stress response in females. While a general lack of effect was noted in response to CMS, this was interpreted as a strong influence of housing and supportive early life experiences in protecting the female rat from the establishment of stress effects related to depression and anxiety. The housing practices employed here may be considered a model of stress-resilience and represents an encouraging avenue of future research.
Keywords: Stress; Depression; Female; Rat; Chronic Mild Stress; Gestational Stress; Anxiety; Social Housing; Estrous Cycle; Weight; Maternal Behaviour; Anhedonia